Pacific history - Coutts, Brent; Fitness, Nicholas (2018)
"Pacific History presents to New Zealand students significant events and issues in Pacific history. Each context includes contested events that have impacted on the people in the Pacific and shaped their place in the modern world. These issues stimulate inquiry and enable students to achieve excellence. Pacific History contains engaging primary sources, a wide range of activities to engage all learners and historiography."--Publisher description.